Implementasi Project-based Learning untuk Meningkatkan Entrepreneurial Mindset dan Entrepreneurial Skills pada Siswa SMK Nurul Islam - Inayah Ilahiyyah; Sri Setyo Iriani; Harti Harti; Muchammad Ghozi Izzuddin (Universitas Proklamasi 45, 2022)
In the 5.0 society era, people are required to be able to balance economic progress in solving social problems. A community can be involved through the integration of computing and physical world space to empower the community's economy and solve social problems, especially in the field of education. Rationally, education can affect the development of the economic sector. Entrepreneurship learning from an early age is needed to improve the progress of a country. The presence of entrepreneurial groups can create job opportunities, increase welfare and per capita income, and reduce unemployment. This study aims to find ways to increase the entrepreneurial mindset and entrepreneurial skills through entrepreneurship learning. The method used in this research is action research with a Project-based Learning (PJBL) approach which is applied to class XI students of SMK Nurul Islam in Bicabi Village, Dungkek District, Sumenep Regency, East Java Province with 15 people as informants. The findings in this study indicate that the PJBL produces product development outputs from each team formed and following the Minimum Completeness Criteria (KKM). Therefore, the PJBL plays an important role in increasing the entrepreneurial mindset and entrepreneurial skills of the students in honing their knowledge and skills process to become entrepreneurs.